2015
DOI: 10.5194/isprsannals-ii-3-w5-277-2015
|View full text |Cite
|
Sign up to set email alerts
|

A User-Driven Selection of Vgi Based on Minimum Acceptable Quality Levels

Abstract: ABSTRACT:Despite Volunteered Geographic Information (VGI) activities are now extremely helpful in a number of scientific applications, researchers and decision makers oppose some resistance to the usage of volunteered contributions, due to quality issues. Several methods and workflows have been proposed to face quality issues in different VGI projects, usually built ad-hoc for specific datasets, thus resulting neither extensible nor transferable. In order to overcome this weakness, the authors propose to perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The quality of VGI will continue to be one of the most important barriers to the integration of VGI to authoritative data, and developing generic and flexible solutions such as the system proposed by Bordogna et al (2015) represents one tangible step forward; thus, we envisage that workflow developments will be a key area of research in the future. Standards agencies also need to recognise that there are new sources of spatial data and that existing standards must be adapted to include these sources or new standards must be developed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality of VGI will continue to be one of the most important barriers to the integration of VGI to authoritative data, and developing generic and flexible solutions such as the system proposed by Bordogna et al (2015) represents one tangible step forward; thus, we envisage that workflow developments will be a key area of research in the future. Standards agencies also need to recognise that there are new sources of spatial data and that existing standards must be adapted to include these sources or new standards must be developed.…”
Section: Discussionmentioning
confidence: 99%
“…However, some papers have appeared in which quality assurance workflows have been proposed. For example, Bordogna et al (2015) propose a flexible system that allows users to specify minimum acceptable quality levels based on their requirements (Figure 3). The system contains a series of quality indicators, including both standard …”
Section: Developing Quality Assurance Workflows and Combining Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason a considerable quantity of literature has appeared on this topic (see e.g. Antoniou and Skopeliti, 2015;Bordogna et al, 2015;Flanagin and Metzger, 2008;Jokar Arsanjani et al, 2015a). There is an ISO standard for spatial quality that can be applied to VGI, but additional quality indicators are required due to the characteristics that are specific to VGI.…”
Section: Issues Related To Vgi For Mappingmentioning
confidence: 99%
“…It is possible to impose a set of protocols in active VGI, but this is usually not possible when using passive VGI or CGI, where the data volumes are often larger than in active sources and hence the data need to be filtered if they are to be used. For example, Bordogna et al (2015) demonstrated how input data can be filtered based on minimum quality criteria specified by the user, for example to remove geotagged photographs downloaded from repositories such as Flickr and Panoramio. Hence this chapter limits its focus to active VGI projects, where the role played by protocols can be crucial for the quality of the data collected.…”
Section: Introductionmentioning
confidence: 99%